AN EXPERIMENTAL STUDY ON BIASED COGNITIVE PROCESSING IN ACCIDENTALLY INJURED PATIENTS WITH DIFFERENT POSTTRAUMATIC GROWTH LEVELS - liang, zhenhong; Liu, XiaoHong; Gong, ShuMei (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Various studies have assessed the negative and/or positive changes in the aftermath of traumatic events. Accidentalinjuries (such as accidents, injuries, etc.), for its high incidence and disability rate, is easy to cause serious psychological problemsand hinder the physical and psychological rehabilitation of the patients.Material and Methods: To explore the characteristics of attention bias in accidentally injured patients with different levels ofPosttraumatic growth (PTG), total score of PTG was adopted to screen out 15 high-PTG group and low-PTG group respectivelyamong accidentally injured patients. Dot probe task was used with positive, negative and neutral facial expression pictures asexperimental materials. An experimental design of 2 (facial expression: positive and negative)×2 (consistency of probe point andfacial expression: consistent and inconsistent)×2 (PTG level: high and low) was employed.Results: Patients with low PTG level had attention bias toward the negative emotional stimuli, and difficulty in distraction from thenegative emotional pictures. The value of D and DI were both significantly greater than 0 (p<0.05). Patients with high PTG level didnot demonstrate significant attention bias toward positive or negative emotional stimuli. The responding time of patients with highPTG level was significantly shorter than that in patients with low PTG level in the incongruent task (p<0.05).Conclusion: There are different characteristics of implicit cognitive processing in patients with different level of PTG, suggestingthe necessity of psychological intervention on the accidentally injured patients.